A theory of change to improve conservation outcomes through CITES - Challender, Daniel W. S.; ’t Sas-Rolfes, Michael; Broad, Steven; Milner-Gulland, E. J. (Frontiers in Ecology and Evolution, 2025)
Understanding the effectiveness of Multilateral Environmental Agreements (MEAs) is critical to addressing international environmental issues. Here we articulate the implied theory of change (ToC) underpinning the design and operation of CITES (Convention on International Trade in Endangered Species of Wild Fauna and Flora), based on an analysis of the Convention’s documented evolution. We use this as a framework to critically evaluate the effectiveness of the Convention, with respect to its stated aims, using a range of theoretical and empirical insights. Although achieving success in various ways, CITES is proving ineffective at deterring illegal and/or unsustainable exploitation of many listed species for international trade, which we attribute to implementation and compliance issues and the Convention’s design, including a principal focus on deterrence through state-led law enforcement. Informed by this analysis we develop a modified ToC which could support more effective implementation of CITES. This ToC is intended for application at the species level and incorporates an in-depth examination of the social-ecological systems (SESs) within which species are harvested, used, and traded. This species-system ToC explicitly considers formal and informal institutions, and the use of institutional diagnostics to inform potential revisions to institutional arrangements along supply chains. We argue that taking this approach when considering whether and how to implement trade measures under CITES could enhance the effectiveness of these measures in reducing overexploitation and support legal, traceable, and more ecologically and socially sustainable international trade in wild species. Finally, we highlight the role that CITES could play in the broader global biodiversity governance regime; better alignment with other relevant MEAs could lead to more effective biodiversity conservation overall.